Effect of Fertilizer Application on Growth and Biomass Production of Ailartthils excelsa on an Arid Land - Gupta, G N; Singh, Neelu; Bohra, N K; Singh, Bilas (Annals of Arid Zone, 2025)
A field experment was conducted on an aridisol in Pali forest Division of Western Rajsthan to study the influence of different nitrogen (0. 9 and 18 g N per trec as urea) and phosphate (0. 3 and 6 g P2O5 per tree as single superphosphate) levels on growth and biomass production of Ailanthus excelsa N18P3 (18 g N + 3 g P2O5 per tree) was the optimum level and increased tree height by 49%, 85% and 35% at one, two and three years of age: collar circumference by 56%, 101% and 11% and crown diameter by 47%,63% and 58% respectively. at three ages. Increase in total biomass production due to this treatment was 181%. at one year and 185% at two year of age . Magnitude of response was higher due to nitrogen application. Combined application of N and I’ had synergistic influence and enhanced the growth. leaf area and root growth of trees.